SAFRA YOLU PATOLOJİLERİNDE ÇOK KESİTLİ BİLGİSAYARLI TOMOGRAFİ İLE ENDOSKOPİK RETROGRAD KOLANJİOPANKREATOGRAFİ BULGULARININ KARŞILAŞTIRILMASI - ÖZTÜRK, FATMA (Fırat Üniveristesi, 2010)
Biliyer sistem hastalıkları günlük pratikte sık karşılaşılan, en sık obstrüksiyona bağlı olarak sarılık, sağ üst kadran ağrısı, bulantı-kusma gibi yakınmalara neden olan, dikkatli ve hızlı şekilde nedeni ortaya konularak tedavi edilmesi gereken bir grup hastalıktır. Hastanın tanı ve tedavisinde tıkanmanın varlığı ve düzeyinin belirlenmesi önemlidir.Biliyer sistemin görüntülenmesinde `altın standart' perkütan transhepatik kolanjiografi (PTK) ya da endoskopik retrograd kolanjiopankreotografi (ERKP) yoluyla biliyer sistemin direkt opasifikasyonu olup invaziv yöntemlerdir. Son yıllarda bilgisayarlı tomografi (BT) ve manyetik rezonans görüntülemede (MRG) gerçekleşen teknolojik gelişimlerle tanısal amaçlı PTK ve ERKP yerini BT ve MRG ile gerçekleştirilen kolanjiopankreatografilere bırakmıştır. Özellikle çok kesitli bilgisayarlı tomografi (ÇKBT) ile multiplanar görüntü elde edebilme (Multiplanar reformation, MPR) ve değişik yazılımlarla farklı pencere aralıklarında görüntü oluşturabilme olanakları (minimum intensity projektion, MinIP) safra yollarının görüntülenmesinde yeni alternatifler oluşturmuştur. Çalışmamızın amacı, safra yolu patolojisi düşünülen olgularda MPR ve MinIP tekniklerini kullanarak ÇKBT bulgularını altın standart olan ERKP ile karşılaştırarak ÇKBT'nin tanısal değerini araştırmaktır.Çalışmaya laboratuar ve klinik bulguları ile safra yolu patolojisi düşünülen ve rutin çekimlerde safra yolu patolojisi tespit edilen 30 olguya ÇKBT çekimi sonrası ERKP yapıldı. MPR ve MinIP tekniklerinde safra yolarının ölçümleri yapılmıştır. ÇKBT'nin, MPR ve MinIP teknikleriyle birlikte patoloji tespitinde, ERKP ile karşılaştırıldığında, pozitif kestirim değeri, negatif kestirim değeri, özgüllük ve duyarlılığı hesaplandı. Patoloji varlığı tespitindeki pozitif kestirim değeri %96.15, negatif kestirim değeri %25, özgüllüğü %50, duyarlılığı %89.28 olarak tespit edildi. ÇKBT'nin obstrüksiyon seviyesini tespiti ERKP ile karşılaştırıldığında %100 uyumlu idi.Çok kesitli bilgisayarlı tomografi, MPR ve MinIP tekniklerin gelişimiyle pankreatobiliyer sistemin değerlendirilmesinde tanısal ERKP'nin yerini alabilecek noninvaziv bir yöntemdir. Ayrıca diğer batın içi organların değerlendirilmesi ve pankreatobiliyer tümörü bulunan hastaların, preoperatif tanısı ve evrelemesinde geniş kapsamlı bilgiler sunmaktadır.Anahtar Kelimeler: Çok kesitli bilgisayarlı tomografi (ÇKBT), safra yolu patolojileri, ERKP, MPR ve MinIP

Biliary tract diseases are a group of diseases commonly encountered in daily practice, most often due to obstruction causing symtoms such as jaundice, right upper quadrant pain, nausea and vomitting should be put out its cause and treated carefully and quickly. The determination of the level and presence of obstruction in the patient?s diagnosis and treatment is important.The ?gold standart? in biliary system imagins is percutaneous transhepatic cholangiography (PTC) or direct opacification of biliary system through the endoscopic retrograde cholangiopancreatography (ERCP) which are invasive methods. In recent years, PTC and ERCP has been abandoned with the technological developments in computed tomography (CT) and magnetic resonance imaging (MRI) and it substituted with cholangiopancreatographies performed with CT and MRI. The facilities which are especially the ability to obtain multiplanar images (multiplanar reformation, MPR) with multi-dedector computed tomography (MDCT) and the image creation with the different softwares in different window intervals (minimum intensity projection, MinIP) have created new alternatives for the biliary tract imaging. The aim of our study is to investigate diagnostic value of MDCT using MPR and MinIP techniques with comparision of MDCT findings and ERCP findings known as the ?gold standart? in patients with suspected biliary tract pathology.30 patients with considered biliary tract pathology according to laboratory and clinical findings, and biliary tract pathology identified after routine imagings were underwent ERCP after MDCT included in this study. Biliary tract measurments were made in MPR and MinIP. When MDCT using with MPR and MinIP techniques in the pathology detection was compared wtih ERCP, the pozitive predictive value, the negative predictive value, specifity and sensivity were calculated. The pozitive predictive value, the negative predictive value, specifity and sensivity were found in the presence of patholgy detection as 96.15%, 25%, 50%, 89.28%, respectively. When compared with ERCP, MDCT was 100% compatible for the detection of obstruction level.Multi-dedector computed tomography with the development of MPR and MinIP techniques is a noninvasive method to replace diagnostic ERCP. In addition, MDCT offers comrehensive informations about other intra-abdominal organs and preoperative diagnosis and staging of patients with pancreatobiliary tumors.Keywords: Multi-dedector computed tomography (MDCT), biliary tract pathology, ERCP, MPR, MinIP
The comparison of findings of multi-dedector computed tomography and endoscopic cholangiopancreatography in bile duct pathologies
Keywords: Radyoloji ve Nükleer Tıp